Analisis keefektifan pembelajaran daring dalam muatan pelajaran PPKn kelas 5 sekolah dasar - Santoso, Sigit; Mahfud, Hasan; Matsuri, Matsuri (Universitas Sebelas Maret, 2022)
The purpose of this study was to determine the effectiveness of online learning on civic education subjects for Class V Elementary School 1 Semali. The subjects of this study were class teachers and students of class V Elementary School 1 Semali, totaling 25 children. There are 3 discussions to determine the effectiveness of online learning, namely the implementation of online learning, the activeness of students when participating in online learning, and student learning outcomes. Data collection techniques in this study included interviews, observation, and document analysis. The data of this study indicate that the implementation of online learning in class V of the State Elementary School 1 Semali is going well, but the students are not active during learning. This results in the teacher's assessment being less than optimal so that student scores tend to decrease during online learning. Based on the data, it can be concluded that the effectiveness of online learning in the subject of Citizenship Education Class V Elementary School 1 Semali for the academic year 2021/2022 is less effective because of the 3 indicators only 1 aspect is in the good category while the other 2 aspects in the poor category and tends to decrease.